Sketch for a typology of the urban adolescent in 1997 (Journal of Parents and Teachers, 1997)
The search for identity in young people is a central theme of the document, which highlights the crisis of knowledge and emotional insecurity they experience. The relevance of close relationships and the self-construction of their identity from diverse cultural influences is underlined. Despite the confusion, values of solidarity and belonging are maintained in their behavior.
Keywords: identity; emotional insecurity; cultural influences; solidarity